Eror Analysis On Inverted Subject And Verb - Lailatus Sa’adah (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2021)
This study focused on investigating the grammatical error, especially inverted subject and verb in English language learning. Moreover, the aim of this study was to investigate the errors and the dominant error of types of inverted subject and verb found based on the students’ test. The data were collected through quantitative design using survey research method that being tested from non-English department students. The participant of this study are 20 students of the first year of soil science department. The result of this survey shows that almost all of the students makes an error in inverted subject and verb. Most of them get 50% of questions that were answered correctly. Few of them answered correctly more than 50%.